Satellite microglia: marker of traumatic brain injury and regulator of neuronal excitability - Alicia B. Feichtenbiner; Karinn Sytsma; Ryan P. O’Boyle; Rhonda Mittenzwei; Heather Maioli; Kathryn P. Scherpelz; Daniel D. Child; Ning Li; Jeanelle Ariza Torres; Lisa Keene; Amanda Kirkland; Kimberly Howard; et al. (Journal of Neuroinflammation)
Abstract Traumatic brain injury is a leading cause of chronic neurologic disability and a risk factor for development of neurodegenerative disease. However, little is known regarding the pathophysiology of human traumatic brain injury, especially in the window after acute injury and the later life development of progressive neurodegenerative disease. Given the proposed mechanisms of toxic protein production and neuroinflammation as possible initiators or contributors to progressive pathology, we examined phosphorylated tau accumulation, microgliosis and astrogliosis using immunostaining in the orbitofrontal cortex, a region often vulnerable across traumatic brain injury exposures, in an age and sex-matched cohort of community traumatic brain injury including both mild and severe cases in midlife. We found that microglial response is most prominent after chronic traumatic brain injury, and interactions with neurons in the form of satellite microglia are increased, even after mild traumatic brain injury. Taking our investigation into a mouse model, we identified that these satellite microglia suppress neuronal excitability in control conditions but lose this ability with chronic traumatic brain injury. At the same time, network hyperexcitability is present in both mouse and human orbitofrontal cortex. Our findings support a role for loss of homeostatic control by satellite microglia in the maladaptive circuit changes that occur after traumatic brain injury.